In situ sustained release of icariin from injectable thermosensitive PLGA-PEG-PLGA hydrogels combined with core decompression for steroid-induced osteonecrosis of femoral head - Xu, Yingxing; Xu, Kaige; Wang, Zehua; Tang, Xinyu; Jiang, Yaping; Li, Tao (Frontiers in Pharmacology, 2025)
BackgroundIcariin (ICA) has showed the beneficial effects on preventing the occurrence of steroid-induced osteonecrosis of the femoral head (SONFH) through enhancing bone formation and remodeling. In addition, the glucocorticoid-induced inhibition of cell proliferation and apoptosis are closely related to the pathogenesis of SONFH. In view of this, the present study was first designed to observe the effect of ICA on dexamethasone (Dex)-induced BMSCs and further reveal the relevant molecular mechanism. Furthermore, due to that the traditional oral administration of ICA is difficult to be absorbed and has a low bioavailability, the sustained-release ICA delivery system co-loaded thermosensitive PLGA-PEG-PLGA hydrogels was constructed, and the efficiency of this drug delivery system for the treatment of early SONFH was evaluated in rats model.MethodsThe anti-apoptotic effect of ICA on the Dex-induced BMSCs was observed by crystal violet staining assay, Hoechst 33342 staining and flow cytometry analysis. Meanwhile, the protein expression levels of Akt/Bad/Bcl-2 signaling pathway were detected by Western blotting. Moreover, the sustained-release ICA delivery system co-loaded thermosensitive PLGA-PEG-PLGA hydrogels was constructed, and the sol-gel transition, in vitro degradation, as well as the sustained release of ICA from this drug delivery system was evaluated by a high performance liquid chromatography (HPLC) system. Ultimately, the sustained-release 2000 μM ICA delivery system co-loaded 25 wt% thermosensitive PLGA-PEG-PLGA hydrogels was injected into the femoral head and medullary cavity after core decompression (CD) to systematically assess the efficiency of this drug delivery system for the treatment of SONFH in rats model by MRI, Micro-CT and histological analysis.ResultsICA could rescue BMSCs from Dex-induced apoptosis through promoting the phosphorylation of Akt/Bad/Bcl-2 signaling pathway. Furthermore, the degradation of copolymer was related to the ICA concentration, and the sustained-release effect of this delivery system in vitro was influenced by the drug and gel concentration. Importantly, the local injection of the sustained-release ICA delivery system co-loaded thermosensitive PLGA-PEG-PLGA hydrogels combined with core decompression (CD) could significantly relieve the bone marrow edema, augment the trabeculae bone, reduce the empty lacunae, and decrease the accumulation of adipocyte while increasing the expression of Runx-2 and inhibiting the expression of PPAR-γ in the femoral head.ConclusionOur data showed that local injection of this sustained-release drug delivery system combined with CD could significantly relieve the glucocorticoid-induced early osteonecrosis in the rats model with SONFH by increasing the residence time of ICA in the necrotic area of femoral head to maximize the anti-apoptotic, pro-osteogenic and anti-adipogenic effects of ICA.